Contractor’s specific problems of social insurance in the context of the lack of the contractor’s obligation to personally provide work - Ceglarska-Jóźwiak, Joanna (Acta Universitatis Lodziensis. Folia Iuridica, 2019)
The article presents contractor’s specific problems of social insurance resulting from the lack of the contractor’s absolute obligation to provide work on a personal basis. The analysis covers some situations in which the contractor provides a service through a third party or the contractor is substituted by a third party. Discussed are the effects of using by the contractor the help of other persons in the sphere of social insurance for the contractor themselves and their assistant, subcontractor or replacement. The design of the person cooperating in the performance of the contract for services has also been discussed.